Allowable take of black vultures in the eastern United States. Issue 2 (18th December 2018) - Zimmerman, Guthrie S.; Millsap, Brian A.; Avery, Michael L.; Sauer, John R.; Runge, Michael C.; Richkus, Kenneth D.
ABSTRACT: Black vultures ( Coragyps atratus ) have been increasing in density and expanding their range in the eastern United States since at least the 1960s. In many areas, their densities have increased to the level where they are causing damage to property and livestock and the number of requests for allowable take permits has increased throughout these areas. The United States Fish and Wildlife Service (USFWS) requires updated information to help inform the number of take permits that could reduce conflicts while meeting obligations under the Migratory Bird Treaty Act. We expanded analyses used to estimate allowable take in Virginia to cover the range of black vultures in the eastern United States. We used the prescribed take level approach, which integrates demographic rates, population size estimates, and management objectives into an estimate of allowable take. We provide estimates of allowable take at 4 different scales: individual states, Bird Conservation Regions, USFWS administrative regions, and flyways. Our updated population time series provides evidence of rapidly increasing black vulture populations in many regions of the eastern United States, with an overall population estimate of approximately 4.26 million in 2015 in the Atlantic and Mississippi Flyways. Estimated allowable take ranged from a few hundred individuals per year in states at the northern end of the species range to approximately 287, 000/year over the entire eastern United States. The USFWS has no legal mandate regarding the spatial scale at which take should be managed and we found little biological evidence of subpopulation structure for black vultures in the eastern United States. We suggest that allowable take for the species be implemented at a scale that meets stakeholder objectives (e.g., reducing conflict, and ensuring that black vultures are not extirpated from local areas) and is efficient for administrative and monitoring purposes. Published 2018. This article is a U.S. Government work and is in the public domain in the USA. Abstract : We estimated allowable lethal take of black vultures at different spatial scales throughout the eastern portion of the United States. Population size of this species has been increasing rapidly and sustainable allowable take ranged from a few hundred individuals in states along the northern portion of their range to approximately 287, 000 individuals range‐wide in the eastern United States.